Self Help Groups (SHGs)- Bank Linkage Programmes: Focusing on the Inclusion of Financially Excluded People - Panigrahi, Sangram (Indian Journal of Finance, 2010)
Finance is the root of economic growth and credit is considered to be its branch. The latter grow vertically, which helps the former to inflate horizontally. In other words, the rapid growth of finance system depends upon the strong and sound system of credit policy in an economy. Credit is a basic lubricant (Singh 2000) that helps to provide a push to the development process. It is the fourth basic prerequisite after food, cloth and shelter for the development of people. Providing credit to the needy people at the right time, at the right place helps in speed development of the society. As the one third of population in our country is living in rural areas, so there is much necessity for inclusion of rural people in the finance system. Delivery of credit at the doorstep of those who are not covered by the formal banking business, coupled with capacity building, is one of the ways for achieving financial inclusion (Sharma 2009). Inclusive financial system, one that allows broader access to financial services, can lead to faster and more equitable growth. Such a system allows poor households to save and manage their money securely, decreases their vulnerability to economic shocks and allows them to contribute more actively to their development. In India, as far as rural credit system is concerned, it has many dimension and peculiarities and informal source of finance was once the only and dominant from of rural credit. It consists of village moneylenders, landlords, friends and relatives. The appearance of co-operatives, Regional Rural Banks (RRBs) and commercial banks has no doubt reduced the share of informal source of finance to supply credit, but not up to the desired extent. This leads to limp down the growth rate of the rural economy. To solve the above problem, the Self Help Groups-Bank linkage programmes (SBLP) approach of National Bank for Agricultural and Rural Development (NABARD) started in 1992, which not only helps to improve the village economy but also makes the rural finance system more inclusive and sociable for common people. An attempt has made in this study to analyses the progress of SHGs-bank linkage (SBLP) programmes of NABARD in rural India to provide financial service to the helpless and neglected groups and to make un-bankable people bankable. The section-I of the study focuses the rural finance system of the Indian economy. Section-II highlights the achievements and performance of SHGs-bank linkages programmes in the Indian financial system. The section-III of the study analyses the challenges and suggestions to bring some change for socialization of the linkages.